Survival Time To Claim Analysis On Travel Insurance Products (UMRAH) Case Study On PT. Jasindo Syariah KC Medan - Romadhoni, Fajri; Marliyah, Marliyah; Sugianto, Sugianto (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The analysis of survival time to claim carried out on Umrah travel insurance products at PT. Jasindo Syariah KC Medan can help with risk management, where the main purpose of the research is to understand the duration between policy purchase and claim submission, as well as the factors that affect that time. This study was conducted on a sample of 80 Umrah travel insurance policies that met certain criteria, using a quantitative approach. The population in this study is the entire Umrah travel insurance policy and samples are taken purposively based on predetermined criteria. Descriptive and survival analysis, including Kaplan-Meier estimation, log-rank tests, and Cox proportional hazards regression, were applied. The results showed that the average claim time was 22.89 days with significant variation among participants. Factors such as the type of insurance (group vs individual) and claim status have been proven to affect the duration of the claim. This study emphasizes the importance of analyzing claim patterns in risk management and accurate premium determination, as well as improving the quality of sharia insurance services in meeting the needs of Umrah pilgrims.